Physicochemical, Pharmacognostical, Phytochemical, Heavy Metal and Pesticidal Residue Analysis of Angelica glauca Edgew roots: An Approach to Establish Quality Standards Using Advanced Analytical Techniques - Mishra, Arun Kumar; Paliwal, Sarvesh Kumar (Current Analytical Chemistry, 2025)
<span class=
Keywords: heavy metal